Development Of Teaching Materials in The Form of Modules on Basic English Grammar and Reading Based on Local Wisdom to Enhance English Language Skills Towards Character-Building Students at Entrepreneurship High School Chevalier Anasai (ECA) In Anasai Village, Semangga District, Merauke - Marnina; Angla F Sauhenda; Butar Butar, Ranta; Uspayanti, Rezki (Universitas Islam Negeri Palopo, 2025)
English is a foreign language that can be acquired through formal education and functions as a communication medium (Agustin 2011). It encompasses diverse materials and complexities at each proficiency level, and there are numerous challenges and obstacles in the English language acquisition process. The study of English is not solely a governmental initiative to enhance the quality of human resources in Indonesia, particularly students' knowledge, but is also a means for students to address future challenges that necessitate active English usage, both in oral and written forms. The objective of this research is to develop an English learning approach grounded in local wisdom and to produce pedagogical materials in the form of modules for Basic English Grammar and Reading that are valid, practical, engaging, and effective. These materials aim to facilitate students' development of English writing and reading skills and augment their interest in English learning based on local wisdom. This research was conducted at the Entrepreneurship High School Chevalier Anasai (ECA) in Anasai Village, Semangga District, Merauke. The participants comprised 35 Grade X students. This descriptive qualitative study was predicated on classroom learning experiences and literature reviews from various sources. Data analysis techniques involved descriptive analysis based on observations of the teaching and learning processes. Data collection methods included observations, learning documents, and surveys of students and teachers at the institution. Data analysis was performed through data reduction, data presentation, and verification until conclusions were drawn (Sugiyono, 2010). The findings of this research will be compiled into a pedagogical text, which is anticipated to serve as the primary instructional material for English education in Grade X at the Entrepreneurship High School Chevalier in Anasai Village, Semangga District, Merauke. The expected outcome of this research is an enhancement in students' grammar, reading, and writing proficiency in English, as well as the provision of an English textbook as a supporting resource for English learning, both within the classroom and in domestic settings. The output of this research is an English textbook containing reading and writing materials linked to local wisdom for Grade X students at Chevalier Anasai High School, Semangga District.